PERUBAHAN RUMUSAN PASAL 1 AYAT (2) UUD 1945, IMPLIKASI DAN IMPLEMENTASINYA DALAM KETATANEGARAAN - Anwar Cengkeng (Widya Yuridika, 2018)
Problem identified in this research are as mentioned in the following. First, how is sovereignty conception according to article 1 sub article (2) of 1945 Constitution? Second, how is implication of change in article 1 sub article (2) of 1945 Constitution state body that had mandate to perform the sovereignty? And third, how is implementation of sovereignty 1 sub article (2) of 1945 Constitution to the Indonesia constitution system? This research included in the category of normative law research and descriptive analysis in nature. The result of the dissertation are as mentioned in the following, First, the sovereignty of conception adopted in the 1945 constitution is sovereignty of the God, state, peoples, and law. Second, the change of formulation of article 1 sub article (2) 1945 constituion has implications on state body of sovereignty performance. Third, in general conception of sovereignty, according to article 1 sub article (2) 1945 constitution, implementation have in Indonesia constitution system, good in arrangement of paintbrush institute state in 1945 constitution, and also in so many act, except in its bearing with authority of DPR and DPD. Kata Kunci: kedaulatan, demokrasi, dan the rule of law.